Gynecomastia - a literature review of management, diagnosis and treatment - Zuzanna Szumlas; Aleksander Jurek; Łukasz Mrozek; Konrad Klocek; Maciej Zwolski; Krzysztof Puchalski; Bartosz Kostecki; Aleksandra Hajduk (Journal of Education, Health and Sport, 2023)
Introduction and Purpose: Gynecomastia is a common clinical problem that can also be a symptom of many serious disorders. The aim of this study is to analyze the etiology, pathogenesis, diagnostics, as well as pharmacological and surgical treatment, while also addressing the psychological aspect of the condition.